THE IMPACT OF LEADERSHIP ON EMPLOYEE PERFORMANCE IN CONSTRUCTION: A CASE STUDY OF BELTEI CONSTRUCTION COMPANY, PHNOM PENH, CAMBODIA - Loeung, By (jfpublisher, 2024)
Leaders in Cambodia's construction business face obstacles that demand them to employ their leadership style in guiding personnel to operate at high performance levels. This study aims to investigate the impact of different leadership styles on employees’ performances at one private construction company in Cambodia. Design/Methodology/approach: Using convenience sampling, 152 valid structured questionnaires for the quantitative study and 30 unstructured questionnaires for the qualitative study were acquired following distribution. This study used a mixed methods research design. Descriptive and inferential statistics were employed for the quantitative analysis of the data. The inferential statistics of the data were presented using regression analysis and Pearson's correlation to explain both relationships and effects in accordance with the study assumptions. Text analysis using theme analysis for qualitative data. The study found a significant positive correlation between employee performance and four leadership styles (transformational, transactional, autocratic, and democratic) at a private construction company in Cambodia. Autocratic leadership had the lowest standard error and highest adjusted R-square, explaining the most variance in employee performance. The study found that construction workers use a variety of leadership styles, including transformational, transactional, democratic, and autocratic, to manage and resolve issues. Autocratic leadership has the highest correlation with employee performance, followed by democratic, transactional, and transformational styles. This hybrid and mixed leadership styles are used to ensure worker efficiency and safety. The study's value lies in its demonstration of how to apply successful leadership styles to improve employee performance, hence raising productivity and maintaining an inventive work atmosphere.